Challenges to teacher resilience: conditions count. (10th January 2013) - Gu, Qing; Day, Christopher
Abstract : Drawing upon findings of a four‐year national research project on variations in the work and lives of teachers in England, this paper provides empirical evidence which contributes to understandings about the importance of resilience in teachers' work. The experience of resilience as perceived by teachers in this research was that it was neither innate nor stable and was much more than a capacity to survive and thrive in extremely adverse circumstances. Rather, it was perceived as being closely allied to their everyday capacity to sustain their educational purposes and successfully manage the unavoidable uncertainties which are inherent in the practice of being a teacher. Their capacity to be resilient fluctuated as a result of the influences of the personal, relational and organisational settings in which they worked. The findings have implications for initial and in‐service professional development programmes, school leadership and the quality retention of teachers.